Metal laminate
Patent Information
- Application Number
- JP2023551285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-29
- Filing Date
- 2022-09-13
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2042-09-13
AI Technical Summary
【0009】 本発明によれば、電気信号の伝送損失が低減できる平滑な表面の金属膜を有する金属張積層板であって、金属膜の密着性が良好で、回路パターンのファインピッチ化ができ、高精度で微細な回路が形成できる金属張積層板を提供することができる。
Smart Images

Figure 0007637255000008 
Figure 0007637255000009 
Figure 0007637255000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-clad laminate. [Background technology]
[0002] In recent years, as communication speeds and capacity have increased in communication devices such as smartphones, the circuit boards used in these devices are required to have low electrical signal loss, finer pitch circuit patterns, and highly accurate, fine circuit formation. Metal-clad laminates, which are the main material of circuit boards, are formed by laminating a metal film on the surface of a base film made of insulating resin (e.g., copper-clad laminates (CCL)). They are also required to have performance similar to that of the above-mentioned circuit boards. Various improved metal-clad laminates (eg, copper-clad laminates (CCL)) have been proposed (eg, see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-14801 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to reduce the transmission loss of electrical signals, it is effective for the surface of the metal film that serves as the transmission path of the electrical signals to be smooth. However, if the surface of the metal film is smooth, the adhesion (bonding) between the metal film and other layers becomes an issue. Therefore, it is desired to provide a metal-clad laminate that can reduce the transmission loss of electrical signals and has excellent adhesion between the metal film and the base film.
[0005] However, to date, no metal-clad laminate has been provided that satisfies all of the following requirements: a metal film with a smooth surface that can reduce transmission loss of electrical signals, has good adhesion to the metal film, and allows for fine pitch circuit patterns and the formation of highly accurate, fine circuits.
[0006] Therefore, the present invention aims to provide a metal-clad laminate having a metal film with a smooth surface that can reduce transmission loss of electrical signals, which has good adhesion to the metal film, allows for fine-pitched circuit patterns, and enables the formation of highly accurate, fine circuits. [Means for solving the problem]
[0007] As a result of intensive research into solving the above problems, the inventors have found that the above problems can be solved by forming a metal film by at least one of plating, sputtering, and vapor deposition, and by disposing a coating film having a specific surface roughness (Rz) and a layer of an adhesion promoter on the coating film between the metal film and a substrate film, thereby completing the present invention.
[0008] The present invention includes the following aspects. [1] A metal-clad laminate comprising a coating film, a layer of an adhesion promoter, and a metal film laminated in this order on a substrate film, The metal film is formed by at least one of plating, sputtering, and vapor deposition, The metal-clad laminate has a surface roughness (Rz) of 1 μm or less. [2] The metal-clad laminate according to [1], in which the coating film, the layer of adhesion promoter, and the metal film are laminated on both sides of the base film in the following order: metal film, layer of adhesion promoter, coating film, base film, coating film, layer of adhesion promoter, and metal film. [3] The metal-clad laminate according to [1] or [2], wherein the adhesion promoter is at least one compound selected from the group consisting of silane coupling agents, titanium coupling agents, zirconia coupling agents, triazine-based compounds, triazole-based compounds, and imidazole-based compounds. [4] The metal-clad laminate according to any one of [1] to [3], wherein the surface roughness (Rz) of the base film is 1 μm or more and 10 μm or less. [5] The metal-clad laminate according to any one of [1] to [4], wherein the metal film has a surface roughness (Rz) of 0.5 μm or less. [6] The metal-clad laminate according to any one of [1] to [5], wherein the coating film is made of a thermosetting resin. [7] The metal-clad laminate according to any one of [1] to [6], wherein the coating film contains at least one of an epoxy resin, a polyimide resin, and a bismaleimide resin. [8] The metal-clad laminate according to any one of [1] to [7], wherein the coating film has a thickness of at least 0.8 times the surface roughness (Rz) of the base film. [9] The metal-clad laminate according to any one of [1] to [8], wherein the metal film has a thickness of 0.05 μm or more and 10 μm or less.
[10] The metal-clad laminate according to any one of [1] to [9], wherein the base film has a relative dielectric constant of 3.5 or less and a dielectric tangent of 0.004 or less.
[11] The metal-clad laminate according to any one of [1] to
[10] , wherein the coating film has a relative dielectric constant of 3.5 or less and a dielectric tangent of 0.004 or less.
[12] The metal-clad laminate according to any one of [1] to
[11] , wherein the base film has a coefficient of thermal expansion (CTE) of 50 ppm or less.
[13] The metal-clad laminate according to any one of [1] to
[12] , wherein the base film is a liquid crystal polymer (LCP) film, a polyether ether ketone (PEEK) film, a tetrafluoroethylene perfluoroalkyl (PFA) film, or a polyphenylene sulfide (PPS) film.
[14] The metal-clad laminate according to any one of [1] to
[13] , wherein the base film contains a filler.
[15] The metal-clad laminate according to any one of [1] to
[14] , wherein the filler contains at least one of mica, talc, boron nitride (BN), magnesium oxide, and silica.
[16] The metal-clad laminate according to any one of [1] to
[15] , wherein the filler has a plate-like shape.
[17] The metal-clad laminate according to any one of [1] to
[16] , wherein the aspect ratio of the filler is 5 or more and 500 or less.
[18] The metal-clad laminate according to any one of [1] to
[17] , wherein the filler has an average particle size of 20 μm or less.
[19] The metal-clad laminate according to any one of [1] to
[18] , wherein the coating film contains a filler.
[20] The metal-clad laminate according to any one of [1] to
[19] , wherein the metal film is a copper metal film.
[21] The metal-clad laminate according to any one of [1] to
[20] , wherein a surface of the base film and / or the coating film is corona-treated, plasma-treated, or ultraviolet-treated. Effect of the Invention
[0009] According to the present invention, there is provided a metal-clad laminate having a metal film with a smooth surface that can reduce transmission loss of electrical signals, in which the metal film has good adhesion, the circuit pattern can be fine-pitched, and high-precision, fine circuits can be formed. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing an example of the configuration of a metal-clad laminate of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the configuration of the metal-clad laminate of the present invention.
[0011] The metal-clad laminate of the present invention will be described in detail below, but the explanation of the constituent elements described below is one example of one embodiment of the present invention, and the present invention is not limited to these contents. The following definitions of terms apply throughout the specification and claims. The thickness of a substrate film, coating film, metal film, etc. is determined by observing the cross section of the object under a microscope, measuring the thickness at five points, and averaging the measured value.
[0012] (Metal-clad laminate) The metal-clad laminate of the present invention comprises a substrate film, a coating film, a layer of an adhesion promoter, and a metal film laminated in this order on the substrate film. The metal film is formed by at least one of plating, sputtering, and vapor deposition. The surface roughness (Rz) of the coating is 1 μm or less.
[0013] FIG. 1 is a cross-sectional view showing an example of the configuration of the metal-clad laminate of the present invention. The metal-clad laminate 1 has a substrate film 2, a coating film 3, a layer 4 made of an adhesion promoter, and a metal film 5, which are laminated in this order. In the metal-clad laminate of the present invention, the coating film and the metal film may be laminated on both sides of the substrate film. FIG. 2 shows another example of the configuration of the metal-clad laminate of the present invention. The metal-clad laminate 1 of the present invention shown in FIG. 2 is formed by laminating a metal film 5a, a layer 4a of an adhesion promoter, a coating film 3a, a base film 2, a coating film 3b, a layer 4b of an adhesion promoter, and a metal film 5b in this order.
[0014] <Base film> In the present invention, the substrate film is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include insulating resin films such as polyimide film, polyether ether ketone (PEEK) film, polyether ketone (PEK) film, polyether ketone ketone (PEKK) film, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer (PFA) film, tetrafluoroethylene-hexafluoropropylene copolymer (FEP) film, tetrafluoroethylene-ethylene copolymer (ETFE) film, polyphenylene sulfide (PPS) film, aramid film, polyethylene naphthalate film, and liquid crystal polymer film (LCP), and mixture films thereof. Among these, polyether ether ketone (PEEK) film, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer (PFA) film, polyphenylene sulfide (PPS) film, and liquid crystal polymer (LCP) film are preferred from the viewpoint of adhesion and electrical properties. The base film may contain a filler, which will be described in detail below.
[0015] <<Filler>> The substrate film may contain a filler to impart various functions to the substrate, such as strength, insulation, heat resistance, adjustment of the coefficient of thermal expansion (CTE), etc. Examples of the filler include inorganic fillers and organic fillers, which may be used alone or in combination.
[0016] Examples of inorganic fillers include mica, talc, boron nitride, magnesium oxide, silica, diatomaceous earth, titanium oxide, zinc oxide, etc. Among these, inorganic fillers such as mica, talc, boron nitride, magnesium oxide, and silica are preferred.
[0017] The organic filler is not particularly limited, but examples thereof include organic particles such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyamide, polycarbonate, polyimide, polyether ketone, polyether ether ketone, polymethyl methacrylate, liquid crystal polymer, and polytetrafluoroethylene.
[0018] The inorganic filler and the organic filler may be used alone by selecting one from the above, or may be used in combination of two or more. When two or more are combined, the combination may be an inorganic filler and an organic filler.
[0019] The shape of the filler is not particularly limited and can be appropriately selected according to the purpose. For example, the inorganic filler may be a spherical inorganic filler or a non-spherical inorganic filler, but from the viewpoint of the coefficient of thermal expansion (CTE) and film strength, a non-spherical inorganic filler is preferred. The shape of the non-spherical inorganic filler may be any three-dimensional shape other than a spherical shape (almost perfect sphere), and examples thereof include a plate-like, scaly, columnar, chain-like, and fibrous shape. Among them, from the viewpoint of the coefficient of thermal expansion (CTE) and film strength, a plate-like or scaly inorganic filler is preferred, and a plate-like inorganic filler is more preferred. In the case of plate-like or scaly inorganic fillers, the average particle size in the planar direction is preferably 0.05 μm or more and 20 μm or less, more preferably 0.1 μm or more and 15 μm or less, still more preferably 0.1 μm or more and 10 μm or less, and even more preferably 0.1 μm or more and 7 μm or less. In addition, the aspect ratio (average major axis length / average minor axis length), which indicates the planar direction and thickness, is preferably 5 or more and 500 or less, more preferably 20 or more and 500 or less, and still more preferably 40 or more and 500 or less, from the viewpoints of the coefficient of thermal expansion (CTE) and film strength. When the average particle size of the filler is 20 μm or less, the surface roughness of the base film can be reduced, making it easier to form a smooth coating film. If the aspect ratio is 5 or more, it is easy to make the CTE sufficiently small. The larger the aspect ratio, the easier it is to adjust the CTE. However, it is difficult to increase the aspect ratio while reducing the particle size, and the cost of the filler tends to increase, so it is desirable to keep the aspect ratio at 500 or less.
[0020] [Measurement of average particle size and aspect ratio] The average particle size and aspect ratio of the inorganic filler can be determined, for example, by observing the film using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and averaging the measured values at three or more points. The average particle size and aspect ratio of the inorganic filler present in the film (layer) can be determined, for example, by embedding the film in an epoxy resin, then ion milling the cross section of the film using an ion milling device to prepare a sample for cross-sectional observation, and observing the cross section of the obtained sample using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and averaging the measured values at three or more points. The average particle size of the organic filler can be determined by observing a cut surface of the base film under an electron microscope, measuring the maximum diameters of at least 10 particles, and calculating the average value as the average dispersed particle size when dispersed in the resin of the base film by melt-kneading and dispersion.
[0021] The content of the filler in the base film is preferably from 1 vol % to 30 vol % and more preferably from 3 vol % to 25 vol %.
[0022] <<Other ingredients>> In the present invention, the base film may contain any known additives as necessary, such as antioxidants, light stabilizers, ultraviolet absorbers, crystal nucleating agents, plasticizers, and dispersants for fillers.
[0023] <<Characteristics of the base film>> The thickness of the substrate film is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 μm to 250 μm.
[0024] The surface roughness (Rz) of the base film is not particularly limited and can be appropriately selected depending on the purpose, but considering various conditions such as the type and content of the filler contained in the base film to impart various functions to the base film, the surface roughness (Rz) of the base film is 1 μm or more. On the other hand, in order to set the surface roughness (Rz) of the coating film formed on the base film to a desired range, the surface roughness (Rz) of the base film is preferably 10 μm or less. In other words, the surface roughness (Rz) of the base film is preferably 1 μm or more and 10 μm or less. In this specification, the surface roughness (Rz) refers to the ten-point average roughness of the film surface. The ten-point average roughness Rz can be determined based on JIS B 0601:2013 (ISO 4287:1997 Amd.1:2009).
[0025] [Measurement of ten-point average roughness Rz] The ten-point average roughness Rz (μm) of the sheet surface is obtained by measuring the roughness curve of the test piece using a laser microscope, measuring 10 samples from each roughness curve based on JIS B 0601:2013 (ISO 4287:1997 Amd.1:2009), and calculating the average value.
[0026] The dielectric constant and dielectric dissipation factor of the base film are not particularly limited and can be appropriately selected depending on the purpose. However, in order to reduce transmission loss of electrical signals, it is preferable that the dielectric constant is 3.5 or less and the dielectric dissipation factor is 0.004 or less.
[0027] [Dielectric constant and dielectric loss tangent] The relative dielectric constant and dielectric tangent of the base film can be measured by the open resonator method using a network analyzer MS46122B (manufactured by Anritsu) and an open resonator Fabry-Perot DPS-03 (manufactured by KEYCOM) at a temperature of 23°C and a frequency of 28 GHz.
[0028] The coefficient of thermal expansion (CTE) of the base film is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of preventing curling after lamination, however, it is preferable that the CTE be, for example, 50 ppm or less in order to reduce the difference in the coefficient of thermal expansion with the metal to be laminated. The thermal expansion coefficient can be measured in tension mode using a thermomechanical analyzer (Hitachi High-Tech Science Corporation, product name: SII / SS7100) with a load of 50 mN, by raising the temperature from 25°C to 250°C at a rate of 5°C / min, measuring the change in dimensions with temperature, and calculating the linear expansion coefficient from the slope in the range from 25°C to 125°C.
[0029] The surface of the substrate film may be subjected to a surface treatment such as a corona treatment, a plasma treatment, or an ultraviolet treatment in order to improve adhesion to the coating film.
[0030] <Coating film> The surface roughness (Rz) of the coating film is 1 μm or less. The method for measuring the surface roughness (Rz) is as described in the above section "Characteristics of the base film." By making the surface roughness (Rz) of the coating film 1 μm or less, a metal film with a smooth surface can be formed, as will be apparent from the examples described later. In such a metal-clad laminate in which transmission loss can be reduced, the metal film can also have excellent adhesion.
[0031] The coating film is formed by forming a film from a resin composition and curing it. The resin composition for forming the coating film is preferably made of a thermosetting resin. Examples of thermosetting resins include phenolic resins, epoxy resins, urea resins, melamine resins, unsaturated polyester resins, polyurethane resins, polyimide resins, silicone resins, and bismaleimide resins. Among these, from the viewpoints of heat resistance, adhesion, and dielectric properties, a coating film containing at least one of an epoxy resin, a polyimide resin, and a bismaleimide resin is preferable.
[0032] <<Epoxy resin>> Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, and hydrogenated versions of these; glycidyl ester-based epoxy resins such as diglycidyl phthalate, diglycidyl isophthalate, diglycidyl terephthalate, glycidyl p-hydroxybenzoate, diglycidyl tetrahydrophthalate, diglycidyl succinate, diglycidyl adipic acid, diglycidyl sebacate, and triglycidyl trimellitate; ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and the like. Examples of the epoxy resin include, but are not limited to, glycidyl ether-based epoxy resins such as glycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, tetraphenyl glycidyl ether ethane, triphenyl glycidyl ether ethane, polyglycidyl ether of sorbitol, and polyglycidyl ether of polyglycerol; glycidyl amine-based epoxy resins such as triglycidyl isocyanurate and tetraglycidyl diaminodiphenylmethane; and linear aliphatic epoxy resins such as epoxidized polybutadiene and epoxidized soybean oil. In addition, novolac-type epoxy resins such as xylene structure-containing novolac epoxy resins, naphthol novolac-type epoxy resins, phenol novolac epoxy resins, o-cresol novolac epoxy resins, and bisphenol A novolac epoxy resins can also be used.
[0033] Further, examples of epoxy resins that can be used include brominated bisphenol A type epoxy resins, phosphorus-containing epoxy resins, fluorine-containing epoxy resins, dicyclopentadiene skeleton-containing epoxy resins, naphthalene skeleton-containing epoxy resins, anthracene type epoxy resins, tertiary butyl catechol type epoxy resins, triphenylmethane type epoxy resins, tetraphenylethane type epoxy resins, biphenyl type epoxy resins, bisphenol S type epoxy resins, etc. These epoxy resins may be used alone or in combination of two or more.
[0034] <<Bismaleimide resin>> Examples of bismaleimide resins include 1-methyl-2,4-bismaleimidebenzene, N,N'-m-phenylene bismaleimide, N,N'-p-phenylene bismaleimide, N,N'-m-toluylene bismaleimide, N,N'-4,4-biphenylene bismaleimide, N,N'-4,4-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4-diphenylmethane bismaleimide, N,N'-4,4-diphenylpropane bismaleimide, N,N'-4,4-diphenylether bismaleimide, and N,N'-3,3-diphenylsulfone bismaleimide. Further examples include modified bismaleimides obtained by modifying the above-mentioned bismaleimide resins with a compound having a primary amine, and polymers obtained by chain extension of amine-modified products such as dimer acid or trimer acid with maleic anhydride, pyromellitic acid, or the like. As the bismaleimide resin, commercially available compounds can be used. Specifically, for example, BMI-3000, BMI-1500, BMI-2550, BMI-1400, BMI-2310, BMI-3005, BMI-689, BMI-2500, BMI-6000, BMI-6100, and the like manufactured by DESIGNER MOLECURES Inc. can be suitably used.
[0035] The coating film may also contain other components such as fillers and various additives.
[0036] <<Filler>> The coating film may contain a filler to improve heat resistance, control fluidity, etc. The type of filler is not particularly limited and may be appropriately selected depending on the purpose, but for example, the fillers described in the above <<Filler>> column as the filler contained in the above base film may be used. The average particle size of the filler contained in the coating is preferably 0.01 μm to 20 μm, more preferably 0.01 μm to 10 μm, and even more preferably 0.01 to 5 μm, so that the surface roughness (Rz) of the coating satisfies 1 μm or less.
[0037] The content of the filler in the coating film is preferably from 0.1 to 25% by volume, and more preferably from 1 to 20% by volume. Since the coating film is required to have a surface smoothness even greater than that of the base film, it is preferable that the average particle size of the filler used is smaller than that of the base film and that the content is small.
[0038] <<Other ingredients>> In addition to the above-mentioned thermosetting resin and filler, the resin composition may contain a tackifier, a flame retardant, a curing agent, a curing accelerator, a coupling agent, a heat aging inhibitor, a leveling agent, an antifoaming agent, a pigment, a solvent, and the like to an extent that does not affect the function of the resin composition.
[0039] The thickness of the coating film is not particularly limited and can be appropriately selected depending on the purpose, but for example, it is preferably 1 to 100 μm, more preferably 3 to 70 μm, even more preferably 5 to 50 μm, and more preferably 5 to 20 μm. If the coating film has a thickness of 1 μm or more, it can maintain a sufficient uniformity to smooth the surface of the base film, and if it is 100 μm or less, it can increase the peel strength between the base film, the coating film, and the metal film. Furthermore, from the viewpoint of smoothing the surface of the base film and thus the surface of the metal film, and thereby obtaining the desired low loss of electrical signals, the thickness of the coating film is preferably at least 0.8 times the value of the surface roughness (Rz) μm of the base film, more preferably at least 1 time the value of the surface roughness (Rz) μm of the base film, and even more preferably at least 1.2 times the value of the surface roughness (Rz) μm of the base film.
[0040] The dielectric constant and dielectric dissipation factor of the coating film are not particularly limited and can be appropriately selected depending on the purpose. However, for the reason of reducing the transmission loss of electric signals, it is preferable that the dielectric constant is 3.5 or less and the dielectric dissipation factor is 0.004 or less. The methods for measuring the relative dielectric constant and the dielectric loss tangent are as described in the section "<Characteristics of the base film>" of the base film above.
[0041] The surface of the coating film may be subjected to a surface treatment such as a corona treatment, a plasma treatment, or an ultraviolet treatment in order to improve adhesion to the metal film.
[0042] <<Coating film manufacturing method>> A coating film can be produced by forming the resin composition into a film. The resin composition can be produced by mixing an epoxy resin, a polyimide resin, a bismaleimide resin, or the like with other components. The mixing method is not particularly limited as long as the resin composition is homogeneous. Since the resin composition is preferably used in the state of a solution or dispersion, a solvent is usually also used. Examples of the solvent include alcohols such as methanol, ethanol, isopropyl alcohol, n-propyl alcohol, isobutyl alcohol, n-butyl alcohol, benzyl alcohol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and diacetone alcohol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and isophorone; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and mesitylene; esters such as methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; and aliphatic hydrocarbons such as hexane, heptane, cyclohexane, and methylcyclohexane. These solvents may be used alone or in combination of two or more. When the resin composition is a solution or dispersion containing a solvent (resin varnish), it can be smoothly applied to a substrate film and a coating film can be formed, and a coating film of the desired thickness and surface roughness can be easily obtained. When the resin composition contains a solvent, the solid content is preferably 3 to 80% by mass, more preferably 10 to 50% by mass, from the viewpoint of workability including the formation of a coating film. When the solid content is 80% by mass or less, the viscosity of the solution is appropriate, and it is easy to apply uniformly. In a more specific embodiment of the method for producing a coating film, a resin varnish containing the above-mentioned resin composition and a solvent is applied to the surface of a substrate film to form a resin varnish layer, and then the solvent is removed from the resin varnish layer to form a coating film in a B stage state. Here, the coating film being in a B stage state refers to a state in which the resin composition is in an uncured state or a semi-cured state in which a part of the resin composition has started to cure, and refers to a state in which the curing of the resin composition further progresses due to heating or the like. Here, the method for applying the resin varnish onto the substrate film is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include spraying, spin coating, dipping, roll coating, blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, inkjet, and dispensing methods. The coating film in the B stage can be further subjected to heating or the like to form a cured coating film.
[0043] <Layer composed of adhesion promoter> The adhesion promoter that forms the layer made of the adhesion promoter is not particularly limited and can be appropriately selected depending on the purpose as long as it can further increase the adhesion (bonding) between the coating film and the metal film. For example, it is preferable that the adhesion promoter is at least one compound selected from coupling agents such as silane coupling agents, titanium coupling agents, and zirconia coupling agents, as well as compounds such as triazine-based compounds, triazole-based compounds, and imidazole-based compounds (hereinafter, the coupling agents and the compounds described herein are collectively referred to as specific compounds).
[0044] <<Coupling agent>> The coupling agent used in the present invention has a structure in which various organic functional groups and hydrolyzable groups are bonded to a central element (silicon, titanium, and zirconium), but in addition to this, an alkoxide compound in which an alkoxyl group is bonded to a central element, an acylate compound in which an acyl group is bonded, and a chelate compound in which a functional group is coordinately bonded may also be used. Furthermore, an oligomer compound in which these compounds are condensed may also be used.
[0045] Examples of the silane coupling agent used in the present invention include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)ethyltrimethoxysilane, 3-(methylphenyl)ethyltrimethoxysilane, 3-(methylphenyl)ethyltriethoxy ... N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, hexamethyldisilazane, 3-(2-aminoethylaminopropyl)dimethoxymethylsilane, 3-(2-aminoethylaminopropyl)trimethoxysilane, 2-(2-aminoethylthioethyl)diethoxymethylsilane, 2-(2-aminoethylthioethyl)triethoxysilane, 3-[2-(2-aminoethylaminoethylamino)propyl]trimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, imidazolylalkyl-trialkoxysilane, diphenyldimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, trifluoropropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyltriethoxysilane, phenyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.
[0046] Among these, 3-glycidoxypropyltrimethoxysilane, N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, diphenyldimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, and the like are preferred.
[0047] The titanium coupling agent used in the present invention includes titanium tetraisopropoxide, titanium tetra normal butoxide, butyl titanate dimer, titanium tetra-2-ethylhexoxide, titanium dioctyloxybis(octylene glycolate), tetramethyl titanate, titanium acetylacetonate, titanium diisopropoxybis(acetylacetonate), titanium tetraacetylacetonate, titanium diisopropoxybis(ethylacetoacetate), titanium ethylacetoacetate, titanium octanediolate, titanium diisopropoxybis(triethanolamine), titanium Examples of suitable surfactants include titanium triethanolamine, titanium lactate ammonium salt, titanium lactate, polyhydroxytitanium stearate, KR38S (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR44 (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR46B (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR55 (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR9SA (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KRTTS (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR41B (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR138S (manufactured by Ajinomoto Fine-Techno Co., Ltd.), KR238S (manufactured by Ajinomoto Fine-Techno Co., Ltd.), and KR338X (manufactured by Ajinomoto Fine-Techno Co., Ltd.).
[0048] Among these, titanium dioctyloxybis(octylene glycolate), titanium diisopropoxybis(ethyl acetoacetate), polyhydroxytitanium stearate, KR44 (manufactured by Ajinomoto Fine-Techno), KR46B (manufactured by Ajinomoto Fine-Techno), KR55 (manufactured by Ajinomoto Fine-Techno), KR9SA (manufactured by Ajinomoto Fine-Techno), KR41B (manufactured by Ajinomoto Fine-Techno), and the like are preferred.
[0049] Examples of the zirconia coupling agent used in the present invention include zirconium tetra-normal propoxide, zirconium tetra-normal butoxide, zirconium tetraacetylacetonate, zirconium tributoxy monoacetylacetonate, zirconium monobutoxy acetylacetonate bis(ethylacetoacetate), zirconium dibutoxy bis(ethylacetoacetate), zirconium tetraacetylacetonate, zirconium tributoxy monostearate, zirconium chloride compound amino carboxylic acid, zirconium monoacetylacetonate, zirconium bisacetylacetonate, zirconium monoethylacetoacetate, zirconium acetylacetonate bisethylacetoacetate, zirconium acetate, and zirconium monostearate.
[0050] Among these, zirconium dibutoxybis(ethylacetoacetate), zirconium tributoxymonostearate, and the like are preferable.
[0051] <<Triazine compounds>> The triazine-based compound is triazine (C3H3N3) or a derivative thereof. A triazine derivative is a compound in which at least one hydrogen atom of triazine is replaced by another substituent. The triazine compound is preferably a compound represented by the following formula (1) since it can further increase the adhesion between the coating film and the metal film.
[0052] [ka] [R in formula (1)] 1 ,R 2 and R 3 are each independently an optional substituent.
[0053] Examples of the optional substituent include an alkyl group, a hydroxyalkyl group, an aryl group, a benzyl group, an alkoxy group, a hydroxy group, an amino group, a thiol group, a carboxy group, a trialkylsilyl group, a trialkoxysilyl group, or a substituent having these groups. In terms of increasing the adhesion between the coating film and the metal film, R in formula (1) 1 ,R 2 is preferably each independently an amino group (-NH2) or a thiol group (-SH). In terms of increasing the adhesion between the coating film and the metal film, R in formula (1) 3 is a trialkoxysilyl group (-Si(OC n H 2n+1 ), n is an integer of 1 or more) or a substituent having a hydroxy group (-OH). Here, the substituent having a trialkoxysilyl group includes an alkylene group having 3 or more carbon atoms and a trialkoxysilyl group, and the substituent having a hydroxyl group includes an alkylene group having 3 or more carbon atoms and a hydroxyl group. The number of carbon atoms of the alkylene group is preferably 10 or less. Specific examples of preferred alkylene groups include, for example, a propylene group, a butylene group, a pentylene group, a hexylene group, a heptylene group, a nonylene group, and a decylene group. Examples of trialkoxysilyl groups include a trimethoxysilyl group, a triethoxysilyl group, a tripropoxysilyl group, and a tributoxysilyl group, and among these, a triethoxysilyl group is preferred. In order to further improve the adhesiveness, R in formula (1) 1 ,R 2 are each independently an amino group or a thiol group, and R 3 is more preferably a substituent having a triethoxysilyl group (-Si(OC2H5)3) or a substituent having a hydroxy group. R in formula (1) 1 ,R 2 are both thiol groups, and R 3A specific example of a compound having a triethoxysilyl group as a substituent is triethoxysilylpropylaminotriazinedithiol.
[0054] <<Triazole compounds>> The triazole-based compound is triazole (C2H3N3) or a derivative thereof. A triazole derivative is a compound in which at least one hydrogen atom of triazole is replaced with another substituent. The other substituents may be bonded to each other to form a ring structure. The triazole-based compound is preferably a compound represented by the following formula (2), since it can further increase the adhesion between the coating film and the metal film.
[0055] [ka] [R in formula (2)] 4 and R 5 are each independently an optional substituent.
[0056] The optional substituents in formula (2) are the same as those in formula (1). In terms of increasing the adhesion between the coating film and the metal film, R in formula (2) 4 is preferably a methyl group (-CH3) or a carboxy group (-COOH). In terms of increasing the adhesion between the coating film and the metal film, R in formula (2) 5 represents an aminoalkyl group in which the hydrogen atom attached to the nitrogen atom may be substituted (-C m H 2m NR 9 2. R 9 are each independently a hydrogen atom, an alkyl group or a hydroxyalkyl group, and m is an integer of 1 or more. R 9 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, and a 2-ethylhexyl group. 9 The hydroxyalkyl group in n Hn OH (n is an integer of 1 or more), and examples thereof include a hydroxymethyl group, a 1-hydroxyethyl group, and a 1-hydroxypropyl group. It is preferable that the above m and n are each independently 4 or less. In order to further improve the adhesiveness, R in formula (2) 4 is a methyl group or a carboxy group, and R 5 More preferably, is an aminoalkyl group.
[0057] <<Imidazole compounds>> An imidazole-based compound is imidazole (C3H4N2) or a derivative thereof. An imidazole derivative is a compound in which at least one hydrogen atom of imidazole is replaced by another substituent. The imidazole compound is preferably a compound represented by the following formula (3), since it can further increase the adhesion between the coating film and the metal film.
[0058] [ka] [R in formula (3)] 6 and R 7 are each independently an optional substituent.
[0059] The optional substituents in formula (3) are the same as those in formula (1). In terms of increasing the adhesion between the coating film and the metal film, R in formula (3) 6 is preferably an alkyl group. 6 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, and a 2-ethylhexyl group, and from the viewpoint of improving adhesiveness, a methyl group (-CH3) is more preferable. In terms of increasing the adhesion between the coating film and the metal film, R in formula (3) 7is preferably a substituent having a trialkoxysilyl group. Examples of the trialkoxysilyl group include a trimethoxysilyl group, a triethoxysilyl group, a tripropoxysilyl group, and a tributoxysilyl group. From the viewpoint of improving adhesion, the substituent having a trialkoxysilyl group is preferably a group in which a trialkoxysilyl group is bonded to one end of an alkylene group, and more preferably a group in which a trimethoxysilyl group (-Si(OCH3)3) is bonded to one end of an alkylene group. Examples of the alkylene group include methylene, ethylene, propylene, and butylene. In order to further improve the adhesiveness, R in formula (3) 6 is a methyl group, and R 7 More preferably, it is a group in which a trimethoxysilyl group is bonded to one end of an alkylene group.
[0060] The adhesion promoter is at least one compound selected from specific compounds, but may be a combination of two or more of the specific compounds. For example, the coupling agent may have a triazine skeleton, a triazole skeleton, or an imidazole skeleton. More specifically, a silane coupling agent having a triazine skeleton, a silane coupling agent having a triazole skeleton, or a silane coupling agent having an imidazole skeleton may also be preferably used.
[0061] <<Method for forming a layer made of adhesion promoter>> The film-forming method for forming a layer made of an adhesion promoter on a substrate is not particularly limited, but examples thereof include a method in which a solution of a specific compound diluted in a solvent is applied to the substrate surface by spray coating, spin coating, dip coating, roll coating, inkjet, etc. In this case, a suitable solvent can be selected depending on the type of the specific compound used, and for example, isopropanol or 1-butanol can be used.
[0062] In addition, the concentration of the specific compound in the diluted solution can be set to any value. However, if the concentration is too high, it becomes difficult to handle and it is difficult to apply it uniformly to the substrate. Conversely, if the concentration is too low, the formed film may not exhibit the desired physical properties. Therefore, the concentration may be set to any value within the range of, for example, 0.001 to 5 mass %.
[0063] Furthermore, the substrate to which the coating film having the adhesion promoter has been applied is heated and dried using a hot air circulating oven (oven), a hot plate, etc. By being heated and dried, the layer made of the adhesion promoter disposed on the substrate exhibits desired physical properties and functions on the substrate surface.
[0064] The thickness of the adhesion-imparting layer is preferably 0.1 to 500 nm, because if it is too thin, it is prone to unevenness, whereas if it is too thick, the strength of the adhesion-imparting layer is insufficient and it is prone to fail to exert adhesive force.
[0065] <Metal film> The metal film is formed by at least one of plating, sputtering, and vapor deposition. By forming a metal film on a coating film having a surface roughness (Rz) of 1 μm or less by at least one of plating, sputtering, and vapor deposition, a metal film with a smooth surface can be formed. Furthermore, metal films formed by these methods enable fine pitch circuit patterns and highly accurate formation of minute circuits. The plating method and the sputtering method may be used separately or in combination. For example, when using them in combination, a thin copper film may be laid down by sputtering, and then a copper film may be formed by electrolytic copper plating.
[0066] The metal constituting the metal film is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include one selected from the group consisting of nickel, copper, silver, tin, gold, palladium, aluminum, chromium, titanium, and zinc, or an alloy containing at least one of these metals. Among these, copper and an alloy containing copper are preferred from the viewpoints of electrical conductivity and economy.
[0067] As described above, the method for forming the metal film includes at least one of plating, sputtering, and vapor deposition. More specifically, examples of the method include vapor deposition films formed by physical vapor deposition (vacuum vapor deposition, sputtering, ion beam vapor deposition, electron beam vapor deposition, etc.) or chemical vapor deposition, and plated films formed by plating. Among them, vacuum vapor deposition films or sputtered films formed by vacuum film formation methods (vacuum vapor deposition, sputtering, etc.), or plated films formed by electrolytic plating are preferred because of their excellent conductivity in the surface direction.
[0068] From the viewpoint of ensuring sufficient electrical signal transmission characteristics and enabling a good fine pitch of the circuit pattern, the thickness of the metal film is preferably 0.05 μm to 20 μm, more preferably 0.1 to 15 μm, and most preferably 0.5 to 10 μm. The surface roughness (Rz) of the metal film on the side not in contact with the layer made of adhesion promoter is not particularly limited and can be appropriately selected depending on the purpose, but for example, it is preferably 0.5 μm or less for the reason of reducing the transmission loss of electrical signals.
[0069] <Effects of metal-clad laminates> Although it is difficult to make the surface of the base film smooth due to the filler contained in the base film and manufacturing reasons, by forming a coating film with a surface roughness (Rz) of 1 μm or less on the base film, the surface of the metal film can be made smooth and the transmission loss can be reduced. Furthermore, the adhesion between the coating film and the metal film can be improved. In the present invention, since a layer made of an adhesion promoter is further formed between the coating film and the metal film, the adhesion (adhesion) between the coating film and the metal film is further improved. The metal film formed on the coating is a thin metal film formed by at least one of plating, sputtering, and vapor deposition, so that it is possible to achieve finer pitches in circuit patterns and to form fine circuits with high precision.
[0070] <Thickness of metal-clad laminate> The thickness of the metal-clad laminate is not particularly limited and can be appropriately selected depending on the purpose, but for example, it is preferably 10 μm or more and 300 μm or less. If the thickness of the metal-clad laminate is equal to or more than the lower limit of the above range, it can have excellent handleability and ensure strength. Also, if it is equal to or less than the upper limit of the above range, it can be made light, thin, short, and flexible.
[0071] <Metal-clad laminate manufacturing method> A coating film is formed on a substrate film. A layer of an adhesion promoter is formed on the surface of the coating opposite to the substrate film. A metal film is formed on the side opposite to the coating of the adhesion promoter layer. A more specific method for forming the coating film is as described above in the section "Coating film manufacturing method", in which a resin varnish containing a resin composition and a solvent is applied to the surface of a substrate film to form a resin varnish layer, and then the solvent is removed from the resin varnish layer to form the coating film. The coating film can be further heated or the like to form a cured coating film. The method for applying the resin varnish is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include spraying, spin coating, dipping, roll coating, blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, inkjet, and dispensing. The method for forming the layer made of the adhesion imparting agent is as described above in the section "Method for forming a layer made of an adhesion imparting agent." Examples of methods for forming the metal film include a vacuum film formation method (vacuum deposition, sputtering) and an electrolytic plating method. From the viewpoint of being able to form a metal film having a desired thickness and surface shape, a method of forming a vapor deposition film by vacuum deposition, a method of forming a plated film by electrolytic plating, a method of forming a sputtered film by sputtering, or a method of combining sputtering and plating by performing sputtering followed by electrolytic plating can be used to form a metal film.
[0072] When the metal-clad laminate of the present invention is a metal-clad laminate having a coating film, a layer of adhesion imparting agent, and a metal film on both sides of a substrate film as shown in Fig. 2, the coating film, the layer of adhesion imparting agent, and the metal film can be formed on one side of the substrate film by the above-mentioned method, and then the coating film, the layer of adhesion imparting agent, and the metal film can be formed on the other side of the substrate film by the same method. Alternatively, a method may be used in which the coating films are formed on both sides of the substrate film together, then a layer of adhesion imparting agent disposed on the coating film is also formed on both sides together, and then a metal film disposed on the layer of adhesion imparting agent is also formed on both sides together.
[0073] When the substrate film and / or coating film is a substrate film or coating film that has been surface-treated by corona treatment, plasma treatment, ultraviolet treatment, or the like, for example, a substrate film may be prepared, the surface of the prepared substrate film may be surface-treated, and a coating film may be formed on the surface-treated substrate film by the above-mentioned method. Alternatively, after forming a coating film, the surface of the coating film may be surface-treated, and then a metal film may be formed by the above-mentioned method. EXAMPLES
[0074] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples. In the following, parts and % are by weight unless otherwise specified.
[0075] Example 1 <Base film> Polyether ether ketone (PEEK) resin (VictrexGranules 450G: manufactured by Victrex) and synthetic mica (Micromica MK100: manufactured by Katakura Agricorp) were mixed so that the synthetic mica was 25% by volume, and the mixture was extruded with a twin-screw extruder to prepare pellets. The average particle size of the synthetic mica used was 4.9 μm, and the aspect ratio was 30 to 50. The obtained pellets were fed into a single-screw extruder equipped with a 900 mm wide T-die, melt-kneaded, and continuously extruded from the T-die to obtain a 100 μm thick PEEK film (film Rz: 6.4 μm, CTE: 30 ppm).
[0076] <Preparation of coating solution 1 for forming coating film> 100 parts by mass of a bismaleimide resin (SLK-3000-T50: Shin-Etsu Chemical Co., Ltd.) with a solid content of 25% by mass, 100 parts by mass of toluene, 60 parts by mass of silica filler (SO-C2: Admatechs), and 2 parts by mass of peroxide (Percumyl D: NOF Corporation) were mixed to obtain coating solution 1.
[0077] <Preparation of copper-clad laminate> The surface of the produced PEEK film was corona-treated. The coating solution 1 obtained above was applied onto the surface-treated PEEK film. The coating film was then dried. The film thickness after drying was 7 μm. Next, the substrate film with the coating was placed in an oven at 200° C. for 1 hour to cure the coating. At this time, the Rz of the coating surface was 0.35 μm. A silane coupling agent (KBM403: Shin-Etsu Chemical Co., Ltd.) adjusted to 1% by weight with ethanol was applied to the cured coating film with a bar coater to a wet thickness of 3 μm and dried to form a layer of adhesion promoter. Furthermore, a copper film (thickness: 0.1 μm) was formed on the adhesion promoter layer by sputtering. The metal layer made of a copper film had an Rz of 0.15 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0078] The peel strength of the metal layer of the metal-clad laminate (copper-clad laminate) of Example 1 thus obtained was measured by the following measurement method, and was found to be 9.8 N / cm. [Peel strength] The peel strength of the copper-clad laminate was measured at a peel rate of 300 mm / min by a T-peel test according to the method specified in JIS K6854-3:1999.
[0079] Furthermore, the transmission loss of the metal-clad laminate (copper-clad laminate) of Example 1 was measured by the following measurement method, and the transmission characteristics were evaluated according to the following criteria. [Transmission loss measurement method] A microstrip line substrate (line length 50 mm) with impedance adjusted to 50 Ω was fabricated from a copper-clad laminate, and the S-parameter (S21) at 20 GHz was measured using a network analyzer. [Evaluation Criteria] ○ (Transmission loss 3.5dB / cm or less: 20GHz) △ (Transmission loss greater than 3.5dB / cm and less than 4dB / cm: 20GHz) × (Transmission loss greater than 4dB / cm: 20GHz)
[0080] Table 1 shows various measurement results for the base film, coating film, layer of adhesion promoter, and metal film in the copper-clad laminate of Example 1, as well as the measurement and evaluation results for the properties of the copper-clad laminate (peel strength and transmission characteristics).
[0081] Example 2 A triazine-based compound (VD-5, manufactured by Shikoku Kasei Corporation, a compound represented by the following formula (1-1) (R10 in the following formula (1-1) is an alkylene group) adjusted to 0.1% by weight with methyl ethyl ketone was applied to the cured coating of a substrate film with a coating prepared in the same manner as in Example 1 using a bar coater to a wet thickness of 3 μm, and then dried to form a layer of adhesion promoter. Furthermore, a copper film (thickness: 0.1 μm) was formed on the adhesion promoter layer by sputtering. The metal layer made of a copper film had an Rz of 0.17 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0082] [ka]
[0083] When the peel strength of the metal layer of the thus obtained metal-clad laminate (copper-clad laminate) of Example 2 was measured, it was 10.2 N / cm.
[0084] Table 1 shows various measurement results for the base film, coating film, layer of adhesion promoter, and metal film in the copper-clad laminate of Example 2, as well as the measurement and evaluation results for the properties of the copper-clad laminate (peel strength and transmission characteristics).
[0085] Example 3 <Base film> Thermoplastic polyimide (PI) resin (Mitsubishi Gas Chemical Co., Ltd., product name: Surprim TO-65) and synthetic mica (Micromica MK100: Katakura Agricorp Co., Ltd.) were mixed so that the synthetic mica was 25% by volume, and the mixture was extruded with a twin-screw extruder to produce pellets. The average particle size of the synthetic mica used was 4.9 μm, and the aspect ratio was 30 to 50. The obtained pellets were fed into a single-screw extruder equipped with a 900 mm wide T-die, melt-kneaded, and continuously extruded from the T-die to obtain a TPI film with a thickness of 100 μm (film Rz: 7.8 μm, CTE: 43 ppm).
[0086] The surface of the prepared TPI film was corona-treated. The coating solution 1 obtained in Example 1 was applied onto the surface-treated TPI film. The coating film was then dried. The film thickness after drying was 9 μm.
[0087] The same procedure as in Example 1 was carried out except that the type of the base film was changed as described above.
[0088] Table 1 shows various measurement results for the base film, coating film, layer of adhesion promoter, and metal film in the copper-clad laminate of Example 3, as well as the measurement and evaluation results for the properties (peel strength and transmission characteristics) of the copper-clad laminate.
[0089] Example 4 <Preparation of coating solution 2 for forming coating film> Coating solution 2 was obtained by dissolving 100 parts by mass of bisphenol A type epoxy resin (Epicron 840-S, manufactured by DIC Corporation), 20 parts by mass of a curing agent (JER Cure 113, manufactured by Mitsubishi Chemical Corporation), 2 parts by mass of 2-ethyl-4-methylimidazole, and 200 parts by mass of methyl ethyl ketone.
[0090] The same procedure was followed as in Example 1, except that Coating Solution 2 was used as described above.
[0091] Table 1 shows various measurement results for the base film, coating film, layer of adhesion promoter, and metal film in the copper-clad laminate of Example 4, as well as the measurement and evaluation results of the properties (peel strength and transmission characteristics) of the copper-clad laminate.
[0092] Example 5 A triazole-based compound (5M-BTA, manufactured by Johoku Chemical Industry Co., Ltd., a compound represented by the following formula (2-1)) adjusted to 0.1% by weight with methyl ethyl ketone was applied to the cured coating of a substrate film with a coating prepared in the same manner as in Example 1 using a bar coater to a wet thickness of 3 μm and then dried to form an adhesion promoter layer. Furthermore, a copper film (thickness: 0.1 μm) was formed on the adhesion promoter layer by sputtering. The metal layer made of a copper film had an Rz of 0.19 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0093] [ka]
[0094] As described above, the same procedure as in Example 1 was carried out except that the type of adhesion promoter was changed.
[0095] Table 1 shows various measurement results for the base film, coating film, layer consisting of adhesion promoter, and metal film in the copper-clad laminate of Example 5, as well as the measurement and evaluation results for the properties (peel strength and transmission characteristics) of the copper-clad laminate.
[0096] Example 6 On the cured coating of the substrate film with a coating prepared in the same manner as in Example 1, an imidazole-based compound (2MUSIZ, manufactured by Shikoku Kasei Co., Ltd., adjusted to 0.1% by weight with methyl ethyl ketone, a compound represented by the following formula (3-1) (R 12 is an alkylene group) was applied to a wet thickness of 3 μm using a bar coater and dried to form a layer of adhesion promoter. Furthermore, a copper film (thickness: 0.1 μm) was formed on the adhesion promoter layer by sputtering. The metal layer made of a copper film had an Rz of 0.16 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0097] [ka]
[0098] As described above, the same procedure as in Example 1 was carried out except that the type of adhesion promoter was changed.
[0099] Table 1 shows various measurement results for the base film, coating film, layer of adhesion promoter, and metal film in the copper-clad laminate of Example 6, as well as the measurement and evaluation results for the properties of the copper-clad laminate (peel strength and transmission characteristics).
[0100] Comparative Example 1 A PEEK film was prepared in the same manner as in Example 1, and the surface of the PEEK film was subjected to a corona treatment. On the surface-treated PEEK film, a copper film (thickness: 0.1 μm) was formed by sputtering. The metal layer made of a copper film had an Rz of 6.2 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0101] The peel strength of the metal layer of the metal-clad laminate (copper-clad laminate) of Comparative Example 1 obtained in this manner was measured by the same method as in Example 1, and was found to be 2 N / cm or less.
[0102] Table 1 shows various measurement results for the base film and metal film of the copper-clad laminate of Comparative Example 1, as well as the measurement and evaluation results for the properties (peel strength and transmission properties) of the copper-clad laminate.
[0103] Comparative Example 2 A copper film (thickness: 0.1 μm) was formed directly on the cured coating of a substrate film with a coating prepared in the same manner as in Example 1 by sputtering without forming an adhesion promoter layer. The metal layer made of a copper film had an Rz of 0.19 μm. Furthermore, copper was deposited on the metal layer by vapor deposition to obtain a metal layer having a thickness of 12 μm.
[0104] The peel strength of the metal layer of the metal-clad laminate (copper-clad laminate) of Comparative Example 2 thus obtained was measured by the following measurement method, and was found to be 6.8 N / cm.
[0105] Table 1 shows the results of various measurements of the base film, coating film, and metal film in the copper-clad laminate of Comparative Example 2, as well as the results of measurements and evaluations of the properties of the copper-clad laminate.
[0106] Comparative Example 3 A copper-clad laminate was produced in the same manner as in Example 1, except that the dry thickness of the coating film was changed to 4.5 μm in Example 1. At this time, the Rz of the surface of the coating film was 1.5 μm.
[0107] Table 1 shows the results of various measurements of the base film, coating film, and metal film in the copper-clad laminate of Comparative Example 3, as well as the results of measurements and evaluations of the properties of the copper-clad laminate.
[0108] [Table 1] Since the metal film in the metal-clad laminate of the present invention produced in the examples has a smooth surface, the metal-clad laminate of the present invention is a metal-clad laminate that can reduce transmission loss. Furthermore, as shown in the results of the above examples, the metal-clad laminate of the present invention has excellent adhesion between the substrate film and the metal film via the layer consisting of the coating film and the adhesion promoter. [Industrial Applicability]
[0109] The metal-clad laminate of the present invention can be suitably used in the production of FPC-related products for electronic devices such as smartphones, mobile phones, optical modules, digital cameras, game consoles, notebook computers, and medical instruments. [Explanation of symbols]
[0110] 1 Metal-clad laminate 2. Base film 3, 3a, 3b coating 4, 4a, 4b Layers made of adhesion promoter 5, 5a, 5b metal film
Claims
1. A metal-clad laminate comprising a base film, a coating film, a layer of an adhesion promoter, and a metal film laminated in this order on the base film, The surface roughness (Rz) of the base film is 1 μm or more and 10 μm or less, The surface roughness (Rz) of the coating film is 1 μm or less, The coating film has a thickness of 5 to 20 μm and a surface roughness (Rz) of the base film x 0.8 or more; The metal film is formed by at least one of plating, sputtering, and vapor deposition, The thickness of the metal film is 0.05 μm or more and 10 μm or less, A metal-clad laminate, wherein the surface roughness (Rz) of the metal film is 0.5 μm or less.
2. 2. The metal-clad laminate according to claim 1, wherein the coating film, the layer of adhesion promoter, and the metal film are laminated on both sides of the base film in the following order: metal film, layer of adhesion promoter, coating film, base film, coating film, layer of adhesion promoter, and metal film.
3. 2. The metal-clad laminate according to claim 1, wherein the adhesion promoter is at least one compound selected from the group consisting of silane coupling agents, titanium coupling agents, zirconia coupling agents, triazine-based compounds, triazole-based compounds, and imidazole-based compounds.
4. The metal-clad laminate according to claim 1 , wherein the coating film is made of a thermosetting resin.
5. The metal-clad laminate according to claim 4 , wherein the coating film contains at least one of an epoxy resin, a polyimide resin, and a bismaleimide resin.
6. 2. The metal-clad laminate according to claim 1, wherein the coating film has a relative dielectric constant of 3.5 or less and a dielectric loss tangent of 0.004 or less.
7. The metal-clad laminate according to claim 1 , wherein the substrate film is a liquid crystal polymer (LCP) film, a polyether ether ketone (PEEK) film, a tetrafluoroethylene perfluoroalkyl (PFA) film, or a polyphenylene sulfide (PPS) film.
8. The metal-clad laminate according to claim 1 , wherein the substrate film contains a filler.
9. The metal clad laminate of claim 1 , wherein the metal film is a copper metal film.
Citation Information
Patent Citations
Flexible copper-clad laminate, flexible printed wiring board for COF, and method of manufacturing them
JP2011014801A
Printed circuit board and manufacturing method thereof
JP2015154073A
Film, metal-clad laminate, flexible substrate, film production method, metal-clad laminate production method, and flexible substrate production method
JP2020110972A
Copper-clad laminate
JP2021008044A
Metal-clad laminate, printed circuit board, and method of manufacturing same
WO2020027189A1